Fractions of Shen-Sui-Tong-Zhi Formula Enhance Osteogenesis Via Activation of β-Catenin Signaling in Growth Plate Chondrocytes - Xu, Rui; Zeng, Qinghe; Xia, Chenjie; Chen, Jiali; Wang, Pinger; Zhao, Shan; Yuan, Wenhua; Lou, Zhaohuan; Lin, Houfu; Xia, Hanting; Lv, Shuaijie; Xu, Taotao; et al. (Frontiers in Pharmacology, 2021)
Background: Shen-sui-tong-zhi formula (SSTZF) has been used to treat osteoporosis for decades and shows excellent clinical efficacy. The aim of this article is to explore the optimal anti-osteoporotic ingredient and the precise mechanisms of SSTZF in mice models. Methods: Ten-week-old female C57BL/6J mice were administrated with each fraction of SSTZF. At 10 weeks after ovariectomy (OVX), the femurs were collected for tissue analyses, including histology, micro-CT, biomechanical tests, and immunohistochemistry for ALP, FABP4 and β-catenin. Additionally, we also evaluated the mRNA expression level of ALP and FABP4 and protein expression level of β-catenin after treated with SSTZF in C3H10T1/2 cells. Moreover, we investigated the anti-osteoporosis effect of SSTZF on mice with β-catenin conditional knockout in growth plate chondrocytes (β-cateninGli1ER mice) through micro-CT, histology and immunohistochemistry analyzes. Results: Significant amelioration of bone loss and fat accumulation were observed in OVX mice with increases in trabecular bone area, ALP content and decreases in lipid drops area and FABP4 content at 10 weeks post-surgery with the treatment of SSTZF normal-butanol extract (SSTZF-NB). Additionally, the elevated β-catenin was revealed in both OVX mice and C3H10T1/2 cells with SSTZF-NB administrated. Furthermore, significant osteoporosis-like phenotype was observed in β-cateninGli1ER mice as expected. However, SSTZF-NB failed to rescue the deterioration in β-cateninGli1ER mice, no significant re-upregulated ALP and FABP4 were observed after treated with SSTZF-NB, demonstrating that SSTZF-NB prevents bone loss mainly via β-catenin signaling. Conclusion: SSTZF-NB enhances osteogenesis mainly via activation of β-catenin signaling in growth plate chondrocytes. SSTZF-NB is the optimal anti-osteoporosis fraction of SSTZF and it can be considered as a salutary alternative therapeutic option for osteoporosis.